Everything is tuberculosis ebook The history and persistence of our deadliest infection. - Green, John (2025)
John Green, the #1 bestselling author of The Anthropocene Reviewed and a passionate advocate for global healthcare reform, tells a deeply human story illuminating the fight against the world’s deadliest infectious disease. Tuberculosis has been entwined with humanity for millennia. Once romanticized as a malady of poets, today tuberculosis is seen as a disease of poverty that walks the trails of injustice and inequity we blazed for it. In 2019, author John Green met Henry Reider, a young tuberculosis patient at Lakka Government Hospital in Sierra Leone. John became fast friends with Henry, a boy with spindly legs and a big, goofy smile. In the years since that first visit to Lakka, Green has become a vocal advocate for increased access to treatment and wider awareness of the healthcare inequities that allow this curable, preventable infectious disease to also be the deadliest, killing over a million people every year. In Everything Is Tuberculosis , John tells Henry’s story, woven through with the scientific and social histories of how tuberculosis has shaped our world—and how our choices will shape the future of tuberculosis.